تشخيص واقع تطبيق ادارة الجودة الشاملة في المستشفيات الجزائرية دراسة ميدانية على مستشفى بشير بن ناصر بولا ية بسكرة- الجزائر- - عمار, أ. بن عيشي (Recherches économiques et managériales; Vol. 11 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2012)
ال ملخص :       تهدف هذه الدراسة إلى تشخيص واقع تطبيق إدارة الجودة الشاملة في المستشفيات الجزائرية، ومن اجل تحقيق ذلك قام الباحث باختيار عينة عشوائية طبقية عددها 203 عامل من مجتمع الدراسة والمتمثل في عدد عمال العاملين مستشفى بشير بن ناصر بولاية بسكرة. وزعت عليهم استبانه وتم التحقق من صدقها وثباتها حيث شملت على 21 فقرة موزعة على أربعة محاور، وهي: التركيز على الزبون) المريض(، التحسين المستمر، التزام الإدارة العليا، إشراك الموظفين،  وتم إدخال البيانات إلى الحاسب الآلي ومعالجتها باستخدام البرنامج الإحصائي spss، وتوصلت الدراسة إلى النتائج التالية: - إدراك العاملون في المتشفيات الجزائرية أهمية تطبيق مبادئ إدارة الجودة الشاملة والمتمثلة في : التركيز على الزبون )المريض( ، التحسين المستمر ، التزام الإدارة العليا ، إشراك الموظفين . - توجد فروق في اتجاهات العاملين في المستشفيات الجزائرية في اداركهم بأهمية تطبيق مبادئ  إدارة الجودة الشاملة تعزى إلى كل من متغير الجنس، العمر، المستوى التعليمي، نوع الوظيفة، الخبرة. الكلمات الدالة: الجودة، إدارة الجودة الشاملة، المتشفيات الجزائرية.   Abstract:     The aim of this study is to diagnose the reality of the application of total quality management in Algerian  hospitals. In order to achieve this, the  tow researcher have selected a stratified random sample of 203 workers from the community of study which is represented by the number of workers employed in Basher  Bennassar Hospital , Biskra. A questionnaire was distributed to them it has been verified to prove its sincerity and persistence .It included over 21 items distributed on the four axes: Focusing on the customer(patient ),continuous improvement, top management commitment, and employee involvement. By entering the data into the computer and processing it using the statistical program SPSS, the study found the following results:  -The workers in Algerian hospitals are quite aware of the importance of the application of total quality management ,namely, focusing on the customer(patient ),continuous improvement, top management commitment, and employee involvement. -There are differences in the trends of workers in the Algerian hospitals concerning their awareness of the importance of applying the Principles of Total Quality Management due to variable of gender, age, education level, job type, experience. Key words: quality, total quality management, Algerian hospitals.